The social dimension of Burnout : social networks in organizations and the development of job Burnout (2020)
Burnout is defined as a multidimensional syndrome that results from chronic exposure to interpersonal stressors on the job. Despite maintaining a conceptual focus on the interpersonal aspects of working in an organization and its influence on burnout, current research on this topic fails to provide a complete picture of the role played by the social dimension of work and how it is related to burnout. There are three particularly important gaps in the literature. First, there is a lack of evidence that social relations act as conduits for demands and resources for workers. Second, extant research neglects to examine the role of those social relations that are the direct result of how work is organized. Third, a clear link is yet to be established between social relations and the evolution of burnout over time. This study aims to understand the connections that exist between the social dimension of work and burnout, where the former is understood as the multiplexity of social relations that individuals manage in their work environment. To achieve this, a two-wave panel study was designed to assess the social networks that are relevant to task interdependence, social support and incivility, and their relationship to experience of burnout in employees. The results suggested that, first, the positions individuals occupy in task-interdependency networks are related to two dimensions of burnout, and second, experiencing burnout might trigger changes in the way that individuals perceive their social networks. Future studies should examine the social, organizational and individual factors that may be involved in complex experiences of burnout, which is understood as the simultaneous experience of its three dimensions